Centennial Anniversary of Mannich's Report on the Formation of β‐Amino‐Ketones in the Archiv der Pharmazie. Issue 7 (July 2017) - Link, Andreas
Abstract : In order to commemorate Carl Mannich's achievement with many implications in the fields of drug design and synthesis, stability of pharmaceutical preparations, and natural product chemistry, we invited researchers to submit their work related to Mannich's pioneering article at the occasion of its centennial anniversary to the Archiv der Pharmazie − where else?